Seasonal variation in the response of a monoecious crop to increased temperature and fertilizers - López-Atanacio, Maribel; Lucas-García, Rodrigo; Rosas-Guerrero, Victor; Alemán-Figueroa, Lorena; Kuk-Dzul, José Gabriel; Hernández-Flores, Giovanni (Frontiers in Plant Science, 2022)
Climate warming may affect the performance of plants directly through altering vegetative or reproductive traits, and indirectly through modifying interactions with their pollinators. On the other hand, the addition of fertilizers to the soil may increase the quantity and quality of floral rewards, favoring the visitation of pollinators and, consequently, the reproductive success of plants. However, it is still unknown whether fertilizers may counteract the effects of increased temperature on the vegetative, floral, and reproductive traits of plants, as well as on the interaction with their pollinators. The aim of this study is to evaluate the effects of the input of organic and synthetic fertilizers on several vegetative and floral traits, and on the rate of legitimate floral visitors and reproductive success of the squash during two seasons, under a scenario of an increase in ambient temperature. During the dry and the rainy seasons, three vegetative, eleven floral, and two reproductive traits, as well as the duration of visits and visitation rate of legitimate floral visitors were evaluated in squash plants distributed into six treatments in a bifactorial design: temperature (ambient or elevated temperature) and fertilizer (organic, synthetic or without supplementary fertilizers). Contrary to our predictions, we found that an increase of ~1.5 °C in ambient temperature, positively influenced several vegetative, floral, and reproductive traits in this crop, and that organic fertilizers, in general, was not better than synthetic fertilizers in improving those traits. Interestingly, the response of the squash and indirectly on their legitimate floral visitors and of squash to the increase of temperature and the input of fertilizers vary widely among seasons, suggesting great temporal variation in plant-pollinator responses to temperature and nutrient availability, which makes food security more unpredictable.